Congruent Molecular and Morphological Diversity of Macaronesian Limpets: Insights into eco-evolutionary Forces and Tools for Conservation - Carreira, Gilberto P.; Shaw, Paul W.; Gonçalves, João M.; McKeown, Niall J. (Frontiers in Marine Science, 2017)
Combined analysis of genetic and morphological variation can provide synergistic insights into eco-evolutionary forces shaping biodiversity, as well as tools for conservation and management. Macaronesian limpets are undergoing severe declines due to overexploitation which calls for an evaluation of the evolutionary significance and taxonomic status of populations. This study details the analysis of genetic (mtDNA sequencing) and morphological (geometric analysis of shell shape) variation among Macaronesian populations of Patella aspera, P. rustica and P. candei. In the case of P. aspera and P. rustica, this also included analysis of mainland conspecifics. mtDNA revealed distinct phylogeographic patterns for the three species. For both P. aspera and P. rustica Macaronesian and continental samples were reciprocally monophyletic, with shallower, and distinct, phylogeographic structure within both clades. For P. candei, the Macaronesian endemic, three reciprocally monophyletic groups corresponding to (i) the Azores, (ii) Madeira and (iii) Selvagens and Canary Islands were resolved. The different patterns for each species are compatible with independent processes of colonisation and demographic processes. Morphological differentiation matched the major phylogeographic groupings (i.e. Macaronesian v Continent for P. aspera and P. rustica; Azores/Madeira/ Selvagens and Canary Islands for P. candei) compatible with such variation being shaped by genetic drift associated with distinct demographic histories of lineages as well as historical/recurrent selection pressures. The genetic/morphological congruence supports the formal recognition of at least three described P. candei subspecies. Moreover, the data prompt recommendation of the separate management of limpets from each archipelago. At present management efforts are hampered by illegal harvesting of limpets. From an applied viewpoint, this study confirms that morphology retains useful information on genetic status and thus represents a potentially cheap method applicable to limpet conservation.